Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $B$ be a Brownian motion and $s\wedge t := \min\{s,t\}$, $s\vee t := \max\{s,t\}$.

I stumbled over the following identity:

$$ \mathbb E[\exp(B(s\wedge t) + B(s\vee t))] \\=\mathbb E[\exp(B(s\wedge t) + B(s\wedge t) + [B(s\vee t) - B(s\wedge t)])] \\=\mathbb E[\exp(2\sqrt{(s\wedge t)} B(1))] \cdot \mathbb E[\exp(\sqrt{\vert t-s \vert}B(1))] $$

Evidently, this result can be obtained by using the scaling relation $B(t)=_d \sqrt{t}B(1)$, but if I try to apply this to the equation I get a different result.

How can one explain this identity?

share|cite|improve this question
up vote 0 down vote accepted

$B(s \vee t)-B(s \wedge t)$ and $2B(s \wedge t)$ are indepedent since the Brownian motion has independent increments. Thus $$\mathbb{E}e(2B(s \wedge t) + B(s \vee t)-B(s \wedge t)) = \mathbb{E}e(2B(s \wedge t)) \cdot \mathbb{E}(B(s \vee t)-B(s \wedge t))$$

Moreover, obviously, $$B(s \wedge t) + B(s \wedge t) = 2 B(s \wedge t) \stackrel{d}{=} 2 \sqrt{s \wedge t} \cdot B(1)$$ by scaling property. Similarly, $$B(s \vee t)-B(s \wedge t) \stackrel{d}{=} B(s \vee t - s \wedge t) = B(|t-s|) \stackrel{d}{=} \sqrt{|t-s|} \cdot B(1)$$ where we used the stationarity of the increments (and again the scaling relation, for the last step).

share|cite|improve this answer

Obviously, $B(s\wedge t)+B(s\vee t)=2B(u)+B'(v)$ with $u=s\wedge t$, $v=s\vee t-s\wedge t=|t-s|$ and $B'(v)=B(v+u)-B(u)=_dB(v)$ while being independent of $B(u)$. The rest follows.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.